On the role played by anticommutativity in Leibniz algebras - Kurdachenko, L.A.; Semko, N.N.; Subbotin, I.Ya. (Доповіді НАН України, 2019)
Lie algebras are exactly the anticommutative Leibniz algebras. We conduct a brief analysis of the approach to Leibniz
algebras which is based on the concept of anticenter (Lie-center) and antinilpotency (Lie nilpotentency). Алгебри Лі являють собою антикомутативні алгебри Лейбніца. Розглянуто короткий аналіз підходу до
алгебри Лейбніца, який базується на концепції антицентра (Лi-центра) та антинільпотентності (Лі-нільпотентності). Алгебры Ли представляют собой антикоммутативные алгебры Лейбница. Рассмотрен краткий анализ
подхода к алгебре Лейбница, который базируется на концепции антицентра (Ли-центра) и антинильпотентности (Ли-нильпотентности).